Echoes of Chongqing : Women in Wartime China - Li, Danke, 1953- (Book collections on Project MUSE., 2010)
This collection of annotated oral histories records the personal stories of twenty Chinese women who lived in the wartime capital of Chongqing during China's War of Resistance against Japan during World War II. The women interviewed came from differing social, economic, and educational backgrounds and experienced the war in a variety of ways, some of them active in the communist resistance and others trying to support families or pursue educations in the face of wartime upheaval. The accounts of how women coped, worked, and lived during the war years in the Chongqing region recast historical understanding of the roles played by ordinary people in wartime and give women a public voice and face that, until now, have been missing from scholarship on the war.